A method to enhance and switch ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical films
By doping Fe3O4 magnetic nanoparticles in the GO film and preparing Fe3O4-GO composite film by vacuum suction filtration, the problem of small and difficult to tune in existing GO materials is solved, and the enhancement and flexible conversion of ultrafast optical nonlinear effects are achieved, and a new magneto-optical medium suitable for high-performance photoelectromagnetic integrated devices is developed.
Patent Information
- Application Number
- CN202111420139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The existing optical nonlinear effects based on GO materials are small and difficult to tune, making it difficult to meet high performance and multifunctional needs.
The Fe3O4-GO composite film was prepared by vacuum suction filtration, and the optical nonlinear effect was tested under different magnetic nanoparticles.
Effectively improve and flexibly convert ultrafast optical nonlinear effects of Fe3O4-GO composite films, and develop a new magneto-optical medium that can be used for saturable absorbers and optical limiting devices.
Smart Images

Figure CN114136902B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of opto-electromagnetic materials, and in particular relates to a method for enhancing and converting ultrafast optical nonlinearity of a Fe3O4-GO composite magneto-optical film. Background Art
[0002] Since the birth of lasers, the nonlinear effects produced by the interaction between strong lasers and media have been continuously discovered and explored by researchers, and the nonlinear effects have been well applied in various fields. In the past few decades, researchers have used nonlinear materials to develop components and applications based on nonlinear absorption effects, such as saturable absorbers in mode-locked lasers, optical limiting devices in laser protection, etc. However, because the current material devices still have problems such as high manufacturing prices, low optical damage thresholds, poor heat dissipation and poor laser resistance, therefore, in order to explore and find new materials with better performance that can replace existing ones, it has important practical significance for achieving high efficiency, high performance and cost reduction of devices.
[0003] Graphene oxide (GO) has become a rising star in the graphene family with its unique physical and chemical properties. Graphene oxide still maintains the layered structure of graphite, but the difference is that hydroxyl (-OH) and epoxy groups are introduced into the graphene sheets, and the edges of the sheets contain carboxyl (-COOH) and carbonyl (-C=O). Although the sp 2 The carbon atom becomes sp 2 With sp 3 The hybridization of carbon atoms and the destruction of large π bonds have caused a decrease in the mechanical and optoelectronic properties of GO, but it is precisely these oxygen-containing functional groups that provide opportunities for surface modification of GO.
[0004] So far, the main preparation methods for GO thin films based on GO solutions include vacuum filtration, spin coating, dip coating and electrostatic self-assembly, etc. Among them, although the GO thin film prepared by vacuum filtration is thicker (generally micrometer level), it is simple to operate, low in cost, excellent in performance, and easy to add suitable nanoparticles or organic matter to the GO solution to obtain hybrid GO thin films, which is increasingly favored by researchers and the industry.
[0005] In order to further expand the wide application of GO-based films in optics, electricity, magnetism and mechanics, a single GO film is difficult to meet the needs of high performance and multifunctionality. It is urgent to produce functionalized GO hybrid films to solve this problem. The chemical functionalization of GO films is caused by oxygen-containing groups in GO, which makes full use of the excellent properties of GO and functionalized materials. A variety of multifunctional materials can be attached to GO films, including organic materials, dye ion molecules, dielectrics, metal nanoparticles and magnetic nanoparticles. Based on the strong coupling effect between GO and functionalized materials, the optoelectronic performance of GO hybrid films will be greatly improved and enhanced. For example, researchers used vacuum filtration to prepare gold nanoparticle-doped GO films. Due to the combined effect of multiple nonlinear mechanisms and photoinduced electron transfer mechanisms, gold nanoparticle hybrid GO films showed several times enhanced optical nonlinear refraction and nonlinear absorption. In addition, researchers used electrostatic self-assembly to prepare composite metamaterials alternating dielectric films and GO films. Through femtosecond micro-nano processing, the controllable reduction of this GO-based hybrid film achieved precise regulation of conductivity, energy band gap and dielectric constant. These studies have laid the foundation for the development of high-performance optoelectronic integrated devices. Although GO-based hybrid films functionalized with metal nanoparticles and dielectric materials can effectively improve their optoelectronic properties, there are few reports on GO hybrid films functionalized with magnetic nanoparticles. By combining the magneto-optical and optoelectronic properties of these composite materials, it is expected not only to tune / improve their optical nonlinearity, but also to achieve enhanced magneto-optical effects and magneto-optical storage density, thereby developing multifunctional integrated devices integrating optoelectronics and magneto-electromagnetic integration. Summary of the invention
[0006] The present invention aims at the problem that the existing optical nonlinear effect based on GO materials is small and difficult to tune, and provides a method for enhancing and converting the ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film. The preparation method is simple in process, low in cost, and mild in conditions. The obtained Fe3O4-GO composite film is evenly dispersed and has a smooth surface. It can effectively enhance and flexibly convert the ultrafast optical nonlinear effect of the Fe3O4-GO composite film and develop a new magneto-optical medium that can be used for saturable absorbers and optical limiting devices. In addition, the experimental test optical path is relatively simple, and the numerical values of the optical nonlinear absorption coefficient and the optical nonlinear refractive index of the sample can be measured, and their sign values can be determined.
[0007] The present invention adopts the following technical solution:
[0008] A method for enhancing and converting ultrafast optical nonlinearity of a Fe3O4-GO composite magneto-optical film comprises the following steps:
[0009] (1) Fe3O4-GO composite films doped with different concentrations of magnetic particles were prepared by vacuum filtration method;
[0010] (2) The prepared composite film was characterized by SEM, XRD, and UV-visible absorption spectroscopy to characterize its morphology and structural characteristics;
[0011] (3) The optical nonlinearity of Fe3O4-GO composite films with different doping concentrations was tested by increasing the magnetic field.
[0012] In the above technical solution, further technical features are as follows:
[0013] The graphene oxide (GO) dispersion used to prepare the Fe3O4-GO composite film has a sheet diameter of 150nm and a concentration of 2mg / ml, and the Fe3O4 magnetic nanoparticle dispersion has a sheet diameter of 150nm and a concentration of 10mg / ml.
[0014] The inorganic alumina filter membrane used in the vacuum filtration method has a diameter of 47 mm and a thickness of 60 mm. , the filter membrane pore size is 100nm.
[0015] The doping dosages of Fe3O4 used to prepare the composite film are 0.01 mL, 0.025 mL, 0.03 mL, and 0.05 mL, respectively.
[0016] The optimized Z scanning optical route is composed of a femtosecond laser, a half-wave plate, a beam splitter, a focusing lens, an electric displacement platform, an adjustable magnetic field device, and an optical power meter (optical power probe I and optical power probe II). A half-wave plate, a beam splitter, a focusing lens, and an optical power probe II are arranged in sequence along the pulse light wave direction of the femtosecond laser. An optical power probe I is arranged on one side of the beam splitter. The Fe3O4-GO composite film is located between the focusing lens and the optical power probe II. The Fe3O4-GO composite film is fixed on the electric displacement platform. The surface of the Fe3O4-GO composite film is perpendicular to the pulse light wave direction. Adjustable magnetic field devices are arranged on both sides of the Fe3O4-GO composite film. The magnetic field device is added on both sides of the material to test the influence of the change of the magnetic field on the optical nonlinearity of the magnetic material.
[0017] The light source is an ultrafast fiber laser (Fianium, W2031) with a wavelength of 532nm, a repetition frequency of 1MHz, a pulse width of 330fs, and a single pulse energy of 1 μ J, the average power is about 1W, and the output spot is 2mm.
[0018] The focal length of the focusing lens is 150 mm.
[0019] The electric displacement platform has a range of 100 mm and a minimum displacement distance of 2.5 μm, which is precisely controlled by computer software. The sample is placed on an electric displacement platform and can move along the -Z to +Z direction, with its Z=0 position coinciding with the focus of the focusing lens. The magnetic field device can be adjusted within the range of 0~4000Oe, and can test the effect of changes in the magnetic field on nonlinear materials containing magnetic materials.
[0020] The optical power meter (Newport 2936-R) records the optical power value, where the reference light enters the optical power probe I to monitor the laser output power change in real time, and the other part of the light finally enters the optical power probe II to achieve third-order nonlinear measurement. The power meter has the characteristics of high sampling rate (250kHz), high resolution (0.0004%), high accuracy (±0.2%), wide frequency measurement range (1Hz-250kHz), etc., and can measure wavelengths of 200nm-1800nm. The optical power meter probe measures power in the range of 20pW-2W, the photosensitive diameter is 3mm, and the maximum energy measured is 5 μ J. It can be seen that the power meter can well meet the characteristics of the light source used in the experiment.
[0021] The movement of the displacement platform and the recording of the experimental data by the optical power probe can both be automated by computer programming.
[0022] The beneficial effects of the present invention are as follows:
[0023] The present invention aims at the problem that the existing optical nonlinear effect based on GO materials is small and difficult to tune, and proposes a method for enhancing and converting the ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film. The preparation method is simple in process, low in cost, and mild in conditions. The obtained Fe3O4-GO composite film is evenly dispersed and has a smooth surface. It can effectively enhance and flexibly convert the ultrafast optical nonlinear effect of the Fe3O4-GO composite film and develop a new magneto-optical medium that can be used for saturable absorbers and optical limiting devices. In addition, the experimental test optical path is relatively simple, and the numerical values of the optical nonlinear absorption coefficient and the optical nonlinear refractive index of the sample can be measured, and their sign values can be determined. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 1 is a comparison of SEM images of the GO film prepared by the present invention and the Fe3O4-GO composite film, wherein (a) is the GO film and (b) is the Fe3O4-GO composite film.
[0025] Figure 2 It is a comparison of the XRD patterns of the GO film prepared by the present invention and the Fe3O4-GO composite film.
[0026] Figure 3It is a comparison of the UV-visible absorption spectrum images of the GO film prepared by the present invention and the Fe3O4-GO composite film.
[0027] Figure 4 It is a comparison of the hysteresis loop images of the GO film prepared by the present invention and the Fe3O4-GO composite film.
[0028] Figure 5 This is a schematic diagram of an experimental optical path of a method for enhancing and converting the optical nonlinear effect of a Fe3O4-GO composite magneto-optical film of the present invention, wherein: 1-femtosecond laser; 2-half-wave plate; 3-beam splitter; 4-optical power probe I; 5-focusing lens; 6-Fe3O4-GO composite film; 7-magnetic field device; 8-optical power probe II.
[0029] Figure 6 The open and closed Z scanning curves of the Fe3O4-GO composite film under different laser energies are measured using the optical path diagram of the present invention.
[0030] Figure 7 The open and closed pore Z-scan curves of the Fe3O4-GO composite film under different magnetic field intensities are measured using the optical path diagram of the present invention. DETAILED DESCRIPTION
[0031] In order to clearly illustrate the technical features of the present invention, the present invention is described in detail below through specific implementation methods and in conjunction with the accompanying drawings.
[0032] Example 1
[0033] A method for enhancing and converting ultrafast optical nonlinearity of a Fe3O4-GO composite magneto-optical film, the method being carried out according to the following steps:
[0034] (1) Fe3O4-GO composite magneto-optical films doped with different concentrations of magnetic particles were prepared by vacuum filtration method;
[0035] (2) The doping dosages of Fe3O4 are 0.01mL, 0.025mL, 0.03mL, and 0.05mL, respectively.
[0036] Example 2
[0037] This embodiment uses the optical path diagram of the present invention to measure the Z scan of open and closed pores of the Fe3O4-GO composite film at different doping concentrations, and the steps are as follows:
[0038] (1) First, fix the experimental sample on the electric displacement platform, then turn on the laser. The pulse light wave emitted by the femtosecond laser becomes parallel light after passing through the beam expansion and collimation system;
[0039] (2) Then, the light passes through a beam splitter, which splits the light into two parts. One part of the light is reflected and enters the optical power sensor I as the reference light, and the other part of the transmitted light beam enters the focusing lens and is focused and incident on the sample surface.
[0040] (3) After passing through the sample, the light beam continues to propagate along the original direction and enters the optical power sensor II. Through computer programming control of the electric displacement platform and the power meter, automatic data recording can be achieved to obtain the Z scan data of the opening.
[0041] (4) By adding a small aperture in front of the optical power sensor II, the closed-aperture Z-scan data can be measured;
[0042] (5) Fe3O4-GO composite films with different doping concentrations were selected and the above operation was repeated for multiple measurements. The curve graph of the experimental data was obtained through the data recorded by the two optical power meter probes and the position of the sample during the movement. The third-order optical nonlinear coefficient of the sample could be further calculated based on the Z-scan curves of the open and closed pores.
[0043] Example 3
[0044] This embodiment uses the optical path diagram of the present invention to measure the Z scan of the open and closed pores of the Fe3O4-GO composite film at different magnetic field intensities, and the steps are as follows:
[0045] (1) Fe3O4-GO composite magneto-optical films doped with different concentrations of magnetic particles were prepared by vacuum filtration method;
[0046] (2) The doping dosages of Fe3O4 are 0.01mL, 0.025mL, 0.03mL, and 0.05mL, respectively.
[0047] Example 4
[0048] This embodiment uses the optical path diagram of the present invention to measure the Z scan of open and closed pores of the Fe3O4-GO composite film at different doping concentrations, and the steps are as follows:
[0049] (1) First, fix the experimental sample on the electric displacement platform, then turn on the laser. The pulse light wave emitted by the femtosecond laser becomes parallel light after passing through the beam expansion and collimation system;
[0050] (2) Then, the light passes through a beam splitter, which splits the light into two parts. One part of the light is reflected and enters the optical power sensor I as the reference light, and the other part of the transmitted light beam enters the focusing lens and is focused and incident on the sample surface. The sample is placed in a magnetic field device with adjustable intensity.
[0051] (3) After passing through the sample, the light beam continues to propagate along the original direction and enters the optical power sensor II. Through computer programming control of the electric displacement platform and the power meter, automatic data recording can be achieved to obtain the Z scan data of the opening.
[0052] (4) By adding a small aperture in front of the optical power sensor II, the Z scan data of the closed aperture can be measured;
[0053] (5) Select Fe3O4-GO composite films with different magnetic field strengths and repeat the above operation for multiple measurements. The curve graph of the experimental data can be obtained through the data recorded by the two optical power meter probes and the position of the sample during the movement. The third-order optical nonlinear coefficient of the sample can be further calculated based on the Z-scan curves of the open and closed pores.
[0054] (1) The Fe3O4-GO composite film prepared in Example 1 was examined by scanning electron microscopy (SEM). The results are shown in the attached figure. Figure 1 .
[0055] By the attached Figure 1 It can be seen that the surface of the GO film is flat and has no wrinkles, indicating that a uniform film was prepared by the vacuum filtration method. In the composite magnetic GO film, the Fe3O4 magnetic nanoparticles are clearly presented on the surface of the GO film, and they are evenly distributed on the entire Fe3O4-GO composite film, and no aggregation is observed, indicating that the quality of the Fe3O4-GO composite film prepared by the vacuum filtration method is very good.
[0056] (2) The Fe3O4-GO composite film prepared in Example 1 was subjected to XRD testing. The results are shown in the attached figure. Figure 2 shown.
[0057] By the attached Figure 2 It can be seen that the pure GO film has peaks corresponding to GO and graphite at 10.52° and 21.72° respectively. In addition to the peaks corresponding to GO and graphite at 10.45° and 24.63°, the Fe3O4-GO composite film has an obvious peak at around 35.15°. After comparing with the XRD standard JCPD card, this peak is the diffraction peak corresponding to iron ions, which further indicates that the Fe3O4-GO composite film was successfully prepared.
[0058] (3) The Fe3O4-GO composite film prepared in Example 1 was subjected to UV-visible absorption spectroscopy testing. The results are shown in the attached figure. Figure 3 shown.
[0059] By the attached Figure 3It can be seen that both GO film and Fe3O4-GO composite film have good linear absorption characteristics in the visible light band. They show absorption resonance peaks and absorption shoulders at around 233nm and 305nm, respectively. However, the absorption of Fe3O4-GO composite film is stronger than that of GO film in the given band. This is mainly caused by the coupling effect between magnetic nanoparticles and GO film. Therefore, Fe3O4-GO composite film is expected to achieve stronger optical nonlinearity and greater magneto-optical effect.
[0060] (4) The Fe3O4-GO composite film prepared in Example 1 was subjected to a hysteresis loop test. The results are shown in the attached figure. Figure 4 shown.
[0061] By the attached Figure 4 It can be seen that there is no hysteresis loop for the GO film in the range of -4000Oe~4000Oe, which is almost a straight line passing through the origin and located in the second and fourth quadrants, indicating that the pure GO film has anti-magnetic properties and is insensitive to external magnetic fields. This is mainly due to the sp 2 With sp 3 The hybridization of carbon atoms causes the Fe3O4-GO composite film to have a good hysteresis loop, with a saturation magnetization of about 0.00085emu / g and a small coercive force (tens of Oe), which proves that the Fe3O4-GO composite film has the characteristics of (sub)ferromagnetism.
[0062] (5) The open and closed pore Z scan data of the Fe3O4-GO composite film prepared in Example 1 at different doping concentrations were fitted and a curve was drawn. The results are shown in the attached figure. Figure 6 shown.
[0063] By the attached Figure 6 It can be seen that the open hole Z scan curves of pure GO film and Fe3O4-GO composite film with a doping dose of 0.01mL have peaks at the focus position, indicating that there is a saturation absorption effect in the composite film, and the saturation absorption effect changes to an anti-saturation absorption effect as the doping concentration increases. The closed hole Z scan curves of pure GO film and Fe3O4-GO composite film with a doping dose of 0.01mL have obvious characteristics of valley first and peak later, indicating the existence of a positive nonlinear refraction (self-focusing) effect, and the self-focusing effect of valley first and peak later changes to peak first and valley later self-defocusing effect as the doping concentration increases. Pure Fe3O4 nanoparticles themselves have no optical nonlinear phenomenon. Therefore, as the concentration of Fe3O4 nanoparticles increases, the mechanism of optical nonlinear enhancement of the composite film comes from the joint action of GO film and Fe3O4 nanoparticles. Fe3O4 nanoparticles can act as a transfer center for energy and electrons, forming a composite structure of electron donor-acceptor with GO film, thereby enhancing the transfer of energy and electrons and improving its optical nonlinearity.
[0064] (6) The data of the open and closed pore Z scans of the Fe3O4-GO composite film prepared in Example 1 under different magnetic field strengths were fitted and a curve was drawn. The results are shown in the attached figure. Figure 7 shown.
[0065] By the attached Figure 7 It can be seen that the open-pore and closed-pore Z scans of the Fe3O4-GO composite film show anti-saturation absorption and self-defocusing effects of peaks first and valleys later, respectively, and they basically show a trend of gradual increase with the increase of the magnetic field. This is because the increase of the magnetic field makes the chaotic magnetic domains of the Fe3O4-GO composite film gradually oriented, which enhances its magnetic moment, thereby enhancing the electron and energy transfer between the Fe3O4 magnetic nanoparticles and the GO film, thereby enhancing its ultrafast optical nonlinear effect. In addition, the incorporation of Fe3O4 magnetic nanoparticles increases the reduction of the GO film, resulting in sp 2 / sp 3 The increase reduces the energy band width of the composite film, thereby improving its ultrafast optical nonlinearity.
[0066] The above specific implementation manner cannot be used as a limitation on the protection scope of the present invention. For those skilled in the art, any substitution, improvement or change made to the implementation manner of the present invention falls within the protection scope of the present invention.
[0067] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film, characterized in that: The method comprises the following steps: In the first step, Fe3O4-GO composite films doped with different concentrations of magnetic particles were prepared by vacuum filtration method; In the second step, the prepared composite film was subjected to SEM, XRD, and UV-visible absorption spectroscopy to characterize its morphology and structural characteristics; The third step is to increase the magnetic field through the optical path device to test the ultrafast optical nonlinearity of Fe3O4-GO composite films with different doping concentrations; The optical path device in the third step includes a femtosecond laser, and a half-wave plate, a beam splitter, a focusing lens and an optical power probe II are sequentially arranged along the pulse light wave direction of the femtosecond laser, an optical power probe I is arranged on one side of the beam splitter, the Fe3O4-GO composite film is located between the focusing lens and the optical power probe II, the Fe3O4-GO composite film is fixed on an electric displacement platform, the surface of the Fe3O4-GO composite film is perpendicular to the pulse light wave direction, and adjustable magnetic field devices are arranged on both sides of the Fe3O4-GO composite film; The light source of the femtosecond laser is an ultrafast fiber laser with a wavelength of 532nm, a repetition frequency of 1MHz, a pulse width of 330fs, a single pulse energy of 1μJ, an average power of 1W, and an output spot size of 2mm; The adjustable range of the magnetic field device is 0~4000Oe.
2. The method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film according to claim 1, characterized in that: In the first step, the graphene oxide dispersion used for the Fe3O4-GO composite film has a flake diameter of 150 nm and a concentration of 2 mg / ml, and the Fe3O4 magnetic nanoparticle dispersion has a flake diameter of 150 nm and a concentration of 10 mg / ml.
3. The method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film according to claim 1, characterized in that: The vacuum filtration method described in the first step uses an inorganic alumina filter membrane with a diameter of 47 mm and a thickness of 60 , the filter membrane pore size is 100nm.
4. The method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film according to claim 1, characterized in that: The doping amounts of Fe3O4 in the prepared composite films were 0.01 mL, 0.025 mL, 0.03 mL, and 0.05 mL, respectively.
5. The method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film according to claim 1, characterized in that: The focal length of the focusing lens is 150 nm.
6. The method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film according to claim 1, characterized in that: The electric displacement platform has a measuring range of 100 mm and a minimum displacement distance of 2.5 μm, and the electric displacement platform moves along the direction of the pulse light wave.
7. The method for enhancing and converting ultrafast optical nonlinearity of Fe3O4-GO composite magneto-optical film according to claim 1, characterized in that: The measuring power range of the optical power probe I and the optical power probe II is 20pW-2W, the photosensitive diameter is 3mm, and the maximum energy measured is 5μJ.
Citation Information
Patent Citations
Carbon / iron oxide composite flexible electrode material and preparation method thereof
CN109860577A